Whither the world : the political economy of the future, volume 2 - Kolodko, Grzegorz W.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The study deals with challenging questions of long-term future of global economy and the mankind. Focusing not only on what happens in the economic sphere but also on cultural, social, political, demographic, technological, and ecological processes. It employs a holistic approach to answer fundamental questions about the course of the future.
Keywords: Science